(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
The paper focuses on annotations jotted down by Vittorio Alfieri in the margins and endpapers of books related to language issues. A chronological path is sketched, from annotations dating from the first years of Alfieri’s « conversion » to literature, to annotations dating from is maturity. Special attention is paid to annotations dating from 1778-1779, where Alfieri carried on intensive studies of Italian language. Four type of annotation are described: lexical annotations; rationalisation of grammars and theorical texts; grammatical observations and ‘petulant’ annotations. Alfieri kept studying Italian language throughout his life: but the way he annotated books concerning language issues gradually changed over the time, as he achieved language proficiency.